1999
DOI: 10.1007/10704282_23
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Sinc-Approximating Kernels for Medical Image Interpolation

Abstract: Abstract. Interpolation is required in many medical image processing operations. From sampling theory, it follows that the ideal interpolation kernel is the sinc function, which is of infinite extent. In the attempt to obtain practical and computationally efficient image processing algorithms, many sinc-approximating interpolation kernels have been devised. In this paper we present the results of a quantitative comparison of 84 different sinc-approximating kernels, with spatial extents ranging from 2 to 10 gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…As was shown in [28] and [30], for filter orders bM=2c > 3 the choice ¼ 5 is very satisfactory in most situations. Later in [29] Meijering compared spline interpolation [36] to sampling theorem based resampling (c.f.…”
Section: A Desoki Et Al: Improved Finite Samples Resampling For Unbmentioning
confidence: 72%
See 1 more Smart Citation
“…As was shown in [28] and [30], for filter orders bM=2c > 3 the choice ¼ 5 is very satisfactory in most situations. Later in [29] Meijering compared spline interpolation [36] to sampling theorem based resampling (c.f.…”
Section: A Desoki Et Al: Improved Finite Samples Resampling For Unbmentioning
confidence: 72%
“…Meijering in [28] showed that the Kaiser windowed sinc filter is one of the best interpolation filters for filter order bM=2c > 3. This filter is defined by…”
Section: Resampling Of Infinite Sequence Of Samplesmentioning
confidence: 99%
“…Finally, the image-intensity values for each voxel are interpolated via a truncated sinc interpolation kernel [68].…”
Section: Image-warping Algorithm-interpolation Of the Fem Solutionmentioning
confidence: 99%
“…Therefore, the approximation order is the main parameter that rules the interpolation quality, as shown by many numerical evidences [6,16,10]. However, the size of the support of ϕ grows with L, thus a tradeoff between interpolation quality and computational complexity has to be achieved.…”
Section: Assessment Of the Interpolation Errormentioning
confidence: 99%